An exploratory study on the relationship between the personal factors of the perpetrator and workplace bullying - Nur ‘Izzati Hidzir; Mastura Jaafar; Alireza Jalali; Norziani Dahalan (Penerbit Universiti Kebangsaan Malaysia, 2017)
Many countries worldwide have considered workplace bullying as an important national agenda. This issue has been extensively discussed by scholars who have determined that bullying severely affects an organization. However, discussions on workplace bullying in the perspective of the perpetrators still remain inadequate. This study aims to examine the relationship between the personal factors and job insecurity of the perpetrator with workplace bullying. It intends to understand the factors that contribute to workplace bullying among Malaysian workers. This research applied the quantitative method of data collection and used SmartPLS M2 version 2.0 to analyse data. The regression analysis showed that personal factors positively affected workplace bullying. In contrast, no significant relationship was found between job insecurity and workplace bullying.